Incidence of Foramen Meningo - Orbitale in South Indian Population - Saraswathy1, K. Yuvaraj Babu*, R. Sivanandan, P. (Recent Research in Science and Technology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Foramen meningo-orbitale is a small inconsistent foramen usually found on the roof or the lateral wall of orbit forming an additional connection between the orbit and the middle cranial fossa. It is usually single but may also be multiple transmitting the orbital branch of middle meningeal artery. In the current study we investigated 97 adult dried human skulls it was found to be present in 43 skulls (44.32%), it was unilateral 27 skulls (27.83%) and found bilaterally in 16 skulls (16.49%). The incidence of this foramen may be of surgical significance for surgeries related to the anterior cranial fossa and also to ophthalmologist.